Natural-RBV e Gestão de RH: os caminhos para a vantagem competitiva sustentável - Lívia Almada Neves (2018)
The limitation of natural resources is an urgent situation. Companies as political, economic and social agents play an important role in global sustainability. Through organizational sustainability, it is possible to consider actions and strategies that can provide a balance in the exploratory relationship between the company and the natural / social / economic / political environment and to achieve a sustainable competitive advantage (SCA). Hart (1995) presents the NRBV theory that provides for the use of rare, valuable, inimitable and organizable resources in terms of pollution prevention, product management and sustainable development strategies. Based on this, this study presents the sustainable strategies as a way to obtain SCA and consequent organizational sustainability. In addition, this study also suggests that Human Resource Management (HRM) may be a moderator that potentiates this relationship between sustainable strategies and VCS because we believe that an environment with a sustainable culture and behavior may be more likely to be able to implement sustainable strategies and, consequently, achieve organizational sustainability and SCA. Therefore, the aim of this study is to verify which NRBV's sustainable strategies can impact on the gain of sustainable competitive advantage on the companies present in the Corporate Sustainability Index (ISE), considering HR management as a potential moderator of this relationship. To do so, it was made a panel analysis of the data of eighteen companies (AES Tietê, Braskem, BRF, Cemig, Copel, CPFL, Duratex, Eletropaulo, EDP, Eletrobras, Ecorodovias, Fibria, Light, Natura, Telefônica, TIM, Tractebel / Engie and WEG) between the years 2013 and 2017. The data correspond to the scores obtained by the companies in the questionnaires that were submitted for submission to the index portfolio and it were obtained directly from GVces which is the index administrator. After analyzing three models, it was verified that the studied companies are achieving SCA with the actions they are carrying out in terms of Sustainable Development strategy, but they need to improve their actions in the strategies of Pollution Prevention and Product Management, because they are not achieving VCS. Regarding HR management, moderation was not confirmed, but a prediction was confirmed in the HRM and SCA ratio. Thus, the companies studied did not present organizational sustainability and consequently also did not contribute to sustainable development and sustainability in global context. In any case, the results of the three models brought very relevant reflections about the actions of the companies during the studied period and how these actions talk with the sustainable strategies for the gain of SCA, pointing out a great incipience in these actions carried out in all models, contributing managerially and academically for the areas of HR management, strategy and finance. The result may reflect Brazil's underdevelopment, but it may also be related to political and economic issues since they are large corporations, with shares in the stock exchange. To further explore the results found it would be necessary to carry out other studies, with qualitative and quantitative approaches. Another gain of this study was the longitudinal analysis that allows to verify the behavior of the companies over time. This type of analysis is not widely used in the areas of HR and Strategy Management, pointing out another methodological possibility for the areas. Future studies may also explore the model proposed in this thesis in micro, small and medium enterprises. The non-identification of the companies can be considered as a limitation, because limited the more detailed analysis of the data. It is also a limitation the period of five years and the fact that it was only possible to carry out a quantitative study. Therefore, this study points out that there is still much to be discussed and researched in terms of sustainability in Brazil.